SISTEM INFORMASI PROGRAM PENDETEKSI DINI GEMPA MELALUI JARINGAN TELKOMSEL DI PROPINSI BENGKULU - Sari, Herlina Latipa; Riyanto, Nugroho Ponco (UNIVED Press, 2013)
Abstract : Judging from the geographical location of Bengkulu Province is a province that is quite commonly found slab cracks of the earth , it is potentially an earthquake tectonic earthquake and tsunami could result in the provincial Bengkulu and surrounding areas . From the sequence of events of the tsunami , never had a history of Bengkulu earthquake on 24 November 1833 Bengkulu been hit by a tsunami with a magnitude 8 earthquake for about 2 minutes and breathing big quake of 8.4 magnitude scale , the quake occurred in 1797 and 1983 were accompanied by tsunami small in the South and North Bengkulu Bengkulu .Information Systems Programs Through Earthquake Early Detection Network Telkomsel At Bengkulu province belong to the category of the good and decent for further use by the user . So with the Information Systems Program Through Earthquake Early Detection Network Telkomsel At the provincial Bengkulu earthquake information regarding can get to the people who use Telkomsel quickly . By looking at the overall results of the calculation of the questionnaire , which shows the percentage of each category , the answer to No Good ( TB ) of 0% , Not Good ( KB ) of 0% , Good ( B ) of 82.5 % and Very Good ( SB ) at 17.5 % . From these percentages can be seen that the Good category ( B ) has the highest percentage is 82.5 % .